Sex Preferences Among Mothers Delivering at Patan Hospital (Kathmandu University Medical Journal, 2012)
Background High sex ratios at birth (SRB) are seen in China, Taiwan, South Korea, parts of India and Vietnam. The imbalance is the result of son preference, accentuated by declining fertility. Prenatal sex determination and female feticides are common in many countries. It is reflected in sex ratio Objective To determine reasons for the preferences for different sex; to find out whether there is altered sex ratio at birth and to find out whether female feticide are common among women who had abortion. Method It is a prospective study. Women who had previous history of abortion and had delivered at Patan Hospital in the year 2066 were interviewed as per questionnaires. Results Among 560 women with total live births of 965, (462 male and 503 female) during their life time the overall sex ratio was 92 male per 100 female birth; total abortions were 663. Preferences for male were 10%, female 15.4% and either was for 74%. The reason for male preference was to continue family lineage, to bring honor, old age security, and performing funeral rites while the reasons for daughter preferences were that they understand mother’s pain, help in household work. The sex ratio of the babies born during the study period was 113 male per 100 female births. The Sex ratio at birth from 1st to 6th deliveries was 61, 79, 101, 210, 286 and 1100 male per 100 female birth respectively. Prenatal sex selection was 8% (by USG) but none had sex selected abortion. ConclusionSex ratio of those delivered during the study period was skewed (136 boys per 100 girls) towards male. There was shift in SRB in 4th and subsequent pregnancies in favor of boys. As the male sex ratio increased the number of induced abortion decreased in subsequent pregnancies.DOI: http://dx.doi.org/10.3126/kumj.v9i4.6334 Kathmandu Univ Med J 2011;9(4):229-232